2007
DOI: 10.1007/s10586-007-0008-9
|View full text |Cite
|
Sign up to set email alerts
|

A high performance integrated web data warehousing

Abstract: Over the years, we have seen a significant number of integration techniques for data warehouses to support web integrated data. However, the existing works focus extensively on the design concept. In this paper, we focus on the performance of a web database application such as an integrated web data warehousing using a well-defined and uniform structure to deal with web information sources including semi-structured data such as XML data, and documents such as HTML in a web data warehouse system. By using a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This helps shifting resources to more critical queries than load jobs. Dung et al (2007) experiment the performance evaluation of an integrated web data warehouse application. Beszedes et al (2003) suggested the technique of program-code compression because the reduced-sized code can have a positive impact on network traffic and embedded system costs such as memory requirements and power consumption.…”
Section: Literature Researchmentioning
confidence: 99%
“…This helps shifting resources to more critical queries than load jobs. Dung et al (2007) experiment the performance evaluation of an integrated web data warehouse application. Beszedes et al (2003) suggested the technique of program-code compression because the reduced-sized code can have a positive impact on network traffic and embedded system costs such as memory requirements and power consumption.…”
Section: Literature Researchmentioning
confidence: 99%
“…A complete classification of all these different types of web contents does not exist. Web content data are updated frequently, volatile and not historical (Bhowmick et al, 1999;Dung, Rahayu, & Taniar, 2007). The creation and maintenance of a data warehouse based on the web content data is needed for effective derived and historical querying of web content data.…”
Section: Introductionmentioning
confidence: 99%